2019
DOI: 10.1016/j.bbrep.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the industrially relevant protease KP-43 with suppressed activity under alkaline conditions developed using expanded genetic codes

Abstract: In the present study, we attempted to control the pH profile of the catalytic activity of the industrially relevant alkaline protease KP-43, by incorporating 3-nitro-l-tyrosine and 3-chloro-l-tyrosine at and near the catalytic site. Thirty KP-43 variants containing these non-natural amino acids at the specific positions were synthesized in Escherichia coli host cells with expanded genetic codes. The variant with 3-nitrotyrosine at position 205, near the substrate binding site, retained its catalytic activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In contact with mycohosts or exposure to their signals, the expression of genes associated with the production of secondary metabolites, hydrolytic enzymes, and other secreted proteins is induced in C. chloroleuca ( 35 , 45 , 46 ). Proteases representing a very diverse group of hydrolases are involved in various cellular processes in organisms ( 1 , 3 , 47 ). In the current study, we found that the serine protease gene CrKP43 was markedly upregulated and expressed both in the highly efficient C. chloroleuca isolate and in mutants lacking the MAPK gene Crmapk under the induction of S. sclerotiorum sclerotia.…”
Section: Discussionmentioning
confidence: 99%
“…In contact with mycohosts or exposure to their signals, the expression of genes associated with the production of secondary metabolites, hydrolytic enzymes, and other secreted proteins is induced in C. chloroleuca ( 35 , 45 , 46 ). Proteases representing a very diverse group of hydrolases are involved in various cellular processes in organisms ( 1 , 3 , 47 ). In the current study, we found that the serine protease gene CrKP43 was markedly upregulated and expressed both in the highly efficient C. chloroleuca isolate and in mutants lacking the MAPK gene Crmapk under the induction of S. sclerotiorum sclerotia.…”
Section: Discussionmentioning
confidence: 99%
“…Employing subtilisin from Bacillus lentus as model protein, regioisomers such as iso-His were generated via a S156C mutant, which did not significantly alter the catalytic properties [ 344 ]. By contrast, the site-specific incorporation of 3NY and 3-chlorotyrosine (3CY) instead of Phe205 near the catalytic center of the subtilisin-like protease KP-43 (S08,123) increased the activity at pH 7 to some extent [ 345 ]. Due to its unique recognition sequence ENLYFQ↓G/S, tobacco etch virus protease (TEV, C04.004) is one of most frequently used enzymes in tailoring recombinant proteins.…”
Section: Modified Proteasesmentioning
confidence: 99%